Limits on Effective Masses of Light and Heavy Majorana Neutrinos for Positron Emitting Modes of Double Beta Decay - Vivekanand; Verma, P.; Chaturvedi, K. (Journal of Scientific Research, 2022)
Double beta decay is a rare weak interaction process in which two identical nucleons inside the nucleus decay with or without the emission of neutrinos. If the neutrinoless double beta decay is observed, the (e+DBD) processes will play a crucial role in discriminating the finer issues like the dominance of Majorana neutrino mass or the right-handed current. In the present work, we have obtained the limits on the effective mass of light and heavy Majorana neutrinos for the electron-positron conversion and double positron-emitting modes of 96Ru, 106Cd, 124Xe, and 130Ba isotopes, using the nuclear transition matrix elements NTMEs M(0ν) and M(0N) for light and heavy Majorana neutrinos obtained in projected Hartree-Fock Bogoliubov (PHFB) model. The predicted half-lives and corresponding extracted limits on heavy neutrino mass is discussed. We have also calculated nuclear sensitivities ξ(0ν) and ξ(0N) due to the light and heavy neutrino exchange, respectively. Finally, the mass limits are obtained using various phase space factors (PSF), and the effect of this PSF on mass limits is discussed.